Impact of COVID-19 convalescence on pregnancy outcomes in patients undergoing IVF/ICSI during fresh ART cycles: a retrospective cohort study - Cao, Mingya; Han, Yan; Feng, Tengfei; Lu, Peiyang; Wang, Yue; Sun, Qingyun; Zhao, Zhiming; Pan, Wensen (Frontiers in Endocrinology, 2024)
Objective The aim was to study the impact of coronavirus disease 2019 (COVID-19) convalescence on female fertility and laboratory and clinical outcomes in fresh assisted reproductive technology (ART) cycles. Methods In this retrospective cohort study, we analyzed data from 294 patients who had recovered from COVID-19 and who underwent fresh ART cycles between January and March 2023 (COVID-19 group). This group was compared with 631 patients who underwent similar ART cycles in the same period in 2022 but without having been infected with COVID-19 (non-COVID-19 group). The analysis focused on comparison of basic demographic characteristics and laboratory parameters of patients in each group. The primary outcome measure was the clinical pregnancy rate, which was examined to assess the impact of COVID-19 infection on the efficacy of ART treatment. Results Basal follicle-stimulating hormone (FSH) levels were significantly lower and antral follicle count (AFC) was markedly higher in the COVID-19 group compared to the non-COVID-19 group (P<0.001 and P=0.004, respectively). The predominant ovarian stimulation protocol in the COVID-19 group was GnRH antagonists (64.85%, P<0.001), with a reduced gonadotropin (Gn) dosage and duration in comparison to the non-COVID-19 group (P<0.05). Although the number of blastocysts formed was lower in the COVID-19 group (P=0.017), this group also exhibited a higher blastocyst freezing rate and a higher rate of high-quality embryos per retrieved oocyte (P<0.001 and P=0.023, respectively). Binary logistic regression analysis indicated that COVID-19 convalescence did not significantly impact clinical pregnancy rates in fresh transfer cycles (odds ratio [OR] = 1.16, 95% confidence interval [CI] = 0.68-1.96, P=0.5874). However, smooth curve-fitting and threshold effect analysis revealed an age-related decline in clinical pregnancy rates in both groups, more pronounced in the COVID-19 group, for women aged over 38 years, with the likelihood of clinical pregnancy decreasing by 53% with each additional year of age (odds ratio [OR] = 0.81, 95% confidence interval [CI] = 0.61–1.08, P=0.1460; odds ratio [OR] = 0.47, 95% CI = 0.21–1.05, P=0.0647). Conclusions Our findings present no substantial evidence of adverse effects on clinical pregnancy outcomes in fresh ART cycles in patients undergoing in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) during the period of convalescence from COVID-19. However, age emerges as a significant factor influencing these outcomes. Notably, for women above 38 years of age, the likelihood of clinical pregnancy in patients with a prior COVID-19 infection decreased by 53% with each additional year. This highlights the importance of considering maternal age, especially in the context of COVID-19, when evaluating the likelihood of successful pregnancy following ART treatments.